Dosimetric factors for diagnostic nuclear medicine procedures in a non-reference pregnant phantom. (7th June 2018) - Rafat-Motavalli, Laleh; Miri-Hakimabad, Hashem; Hoseinian-Azghadi, Elie
Abstract: This study evaluates the impact of using non-reference fetal models on the fetal radiation dose from diagnostic radionuclide administration. The six-month pregnant phantoms including fetal models at the 10th and 90th growth percentiles were constructed at either end of the normal range around the 50th percentile and implemented in the Monte Carlo N-Particle code version MCNPX 2.6. This code has then been used to evaluate the 99m Tc S factors of the target organs of interest, as this is the most commonly used radionuclide in nuclear medicine procedures. Substantial variations were observed in the S factors between the 10th/90th percentile phantoms from the 50th percentile phantom, with the greatest difference being 38.6%. When the source organs were in close proximity to, or inside the fetal body, the 99m Tc S factors presented strong statistical correlations with fetal body habitus. The trends observed in the S factors and the differences between various percentiles were justified by the source organs' masses, and chord length distributions. The results of this study showed that fetal body habitus had a considerable effect on fetal dose (on average up to 8.4%) if constant fetal biokinetic data were considered for all fetal weight percentiles. However, a smaller variation on fetal dose (up to 5.3%) was obtained if the available biokinetic data for the reference fetus were scaled by fetal mass.